Concepção, desenvolvimento e integração de um ambiente SIGWEB com ferramentas de software livre - Bressan, Thiago Santi (2010)
The dynamism and multi-tasking is now the web is necessary systems with the possibility of spatial information in a particular geographical environment with complete user interaction in building its senary information. Innovations are needed to design and develop a system for SIGWeb the spatial information, with support for various areas takes this possibility. The focus is not only to develop a system for web and yes, a generic system capable of being adaptable to various topics that have some type of variable which can be spatialized. The starting this context the system was developed Geom@p@s, using free software tools such as the PostgreSQL database with PostGIS spatial extension related to web programming language PHP (Hypertext Preprocessor) and API (Application Programming Interface) Google Maps. The system Geom@p@s application is a robust and dynamic, adapting to user needs by importing data from the established formats.